Exploring abusive behaviours in lesbian, gay, bisexual and/or transgender relationships - Donovan, Catherine (UK Data Service, 2015)
This collection comprises mixed-methods data from a study exploring the use of abusive behaviours by partners in same-sex, bisexual and/or transgender relationships and practitioners' accounts of and perspectives on developing suitable and inclusive interventions for, and responses to, perpetrators of domestic violence and abuse in same-sex, bisexual and/or transgender relationships.In recent years in the UK there has been recognition that domestic violence and abuse (DVA) takes place in same-sex, bisexual and/or transgender relationships and a parallel and emerging body of research which has begun to explore and develop understandings about how and why this occurs, and whether and how victim/survivors seek help. However, despite this growing literature, there has been no dedicated research on those who are the abusive partners in same-sex, bisexual and/or trans relationships, and consequently there has been little evidence to inform the development of services to address their behaviours. This study, which we have named the Coral Project, is the first UK study to collect data specifically about the perpetration of violent and abusive behaviours in lesbian, gay, bisexual and/or transgender (LGB and/or T) relationships. The aims of the Coral Project were to: explore similarities and differences across sexuality and gender of those who enact ‘abusive’ behaviours in LGB and/or T and heterosexual relationships; do this with those who have enacted ‘abusive’ behaviours as well as practitioners who provide interventions for predominantly heterosexual male perpetrators; explore what methods might work best to elicit data to address these aims; and share key findings with key stakeholders to develop best practice guidance for work with those who use ‘abusive’ behaviours in LGBT relationships. A mixed-methods approach was taken in order to gather both quantitative and qualitative data about the use of abusive behaviours in same-sex, bisexual and/or transgender relationships through a national online survey and follow-up in-depth interviews with volunteers from the survey, respectively. Semi-structured interviews and focus groups with practitioners were also conducted in order to elicit practitioners’ understandings of the use of abusive behaviours within LGB and/or T relationships and their views on the suitability of existing domestic violence perpetrator interventions (designed primarily for heterosexual men) for addressing the abusive behaviour of LGB and/or T individuals, as well as what to find out about the nature of any current provision for LGB and/or T perpetrators and barriers to developing LGB and/or T interventions.